Sex assessment from the proximal femur in the Spanish population based on three-dimensional computed tomography metric analysis - Djorojevic, Mirjana; Roldán, Concepción; Botella, Miguel; Alemán, Inmaculada (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The studies published in recent years have shown that the linear measurements on the three-dimensional computed tomography (3D-CT) clinical images of the hip bone, skull or breastbone can serve as a reliable alternative method for sex estimation. In spite of the fact that the proximal femur exhibited high dimorphism when examining the skeletal material, there is still a lack of morphometric studies dealing with the CT imaging of this anatomical region that would confirm the relevance of the previously obtained results. The aim of this study was to validate the reliability and precision of some proximal femur measurements obtained in vivo from the 3D-CT models and to compare the accuracies of our findings with those formerly reported by other relevant research. Methods. A total of 146 CT scans (73 male and 73 females) were selected to take 6 measurements using the traditional osteometric methods. The 3D reconstruction was done at 1mm and 1.25 mm thick slices with OsiriX (v.4.1). The univariate and multivariate discriminant functions (DFs) were formulated for assessing sex. Results. The vertical diameter of neck and the vertical diameter of head were found to contribute the most when considered independently (90.4%–91.8%). When combining these with the other dimensions, the prediction accuracy increased up to 97.3%. The accuracy of CT measurements is in accordance with those obtained in the traditional morphometric studies on the skeletonized femurs of contemporary populations. The 3D-CT approach showed remarkably higher percentage of predictive ability in comparison with the 2D technique. Conclusion. 3D-CT is a suitable tool for the objective quantification of osteological data. The medical scans and measurements on living individuals offer a valuable source of data from which the highly reliable skeletal standards can be developed for estimating sex, even from the fragmented remains. The method proposed here can be highly useful especially in the identification of mass disaster victims when the direct osteometry is difficult to apply and maceration of the remains is not an option.
Keywords: anthropometry; femur; multidetector computed tomography; sex